development Pengembangan bahan ajar berbasis digital (flipbook) pada materi sapuan, dengkulan, dan guntingan: pencak silat - Made, Gede Agus Saputra; Spyanawati, Ni Luh Putu; Gunarto, Peby (Athena: Physical Education and Sports Journal, 2025)
The traditional martial art of Indonesia is the sport of pencak silat, reflecting the richness of culture and has now become part of the higher education curriculum, including in the TP course. Pencak Silat learning in the Penjaskesrek Study Program, FOK Undiksha. However, the use of digital teaching materials such as flipbooks in lectures is still very limited, although most students state the importance of digitalizing learning. In this research, in order to create learning materials in digital form (flipbooks) on the Sapuan, Dengkulan, and Guntingan materials and to test their feasibility and practicality through the ADDIE style creation approach. The ADDIE method consists of five systematic parts: needs analysis, media design, content creation, product implementation, and effectiveness review. The learning tools created were tested by material experts and media experts, then the product was tested on students with 3 tests, namely: individual testing, then small-scale testing and large-scale testing. The output of this research shows that the interactive flipbook produced, containing writing, photos, recordings, and quizzes, was considered very feasible by the validator and practical to use based on student responses. The conclusion of this study states that the development of flipbooks not only meets the needs of modern learning but also increases students' interest and learning effectiveness. This study contributes to the innovation of learning media in the field of sports and recommends further development of other pencak silat materials using a similar approach